Carbon-13 turnover in 'roxo de valinhos' fig trees - da Silva, Andrea Carvalho; de Souza, Adilson Pacheco; Ducatti, Carlos [UNESP]; Leonel, Sarita [UNESP] (Soc Brasileira Fruticultura, 2011)
The aim of this study was to assess carbon-13 turnover in different organs of the fig tree, 'Roxo de Valinhos' cultivar. The experiment was carried out in an orchard at School of Agronomical Sciences, FCA/UNESP, Botucatu Campus, State of São Paulo, Brazil. The main photosynthetically active leaf was previously determined based on gas exchanges by means of an open portable photosynthesis system, IRGA. That leaf was placed in a chamber where the enriched gas injection occurred. The leaf enrichment time was 30 minutes. Treatments were constituted of seven fig trees removed from the soil after: 6; 24; 48; 72; 120; 168 and 360 hours of enrichment using (13)C, and their parts were sectioned into: apical bud, young leaves, adult leaves (photosynthetically active), lateral sprouts, fruits, and branch. The results allowed the establishment of the carbon-13 metabolism sequence in the studied parts: Young leaves > Fruits > Sprouts > Adult leaves > Apical bud > branch > Labeled leaf. 'Roxo de Valinhos' fig trees, had (13)C turnover of 24 hours and carbon-13 half-time shorter than 11 hours.
Keywords: Ficus carica L.; phisiology; carbohydrates; turnover